2022
DOI: 10.3390/ijerph19094954
|View full text |Cite
|
Sign up to set email alerts
|

One Word to Describe My Experience as a COVID-19 Survivor Six Months after Its Onset: Findings of a Qualitative Study

Abstract: The COVID-19 pandemic emotionally affected the lives of patients cared for in different settings. However, a comprehensive view of the whole experience as lived by survived patients, from the onset of the disease and over time, is substantially unknown to date. A descriptive qualitative design was implemented according to the Standards for Reporting Qualitative Research. Adult patients (=1067) cared for during the first wave (March/April 2020) capable of answering an interview and willing to participate were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…In addition to image metaphors, the present study showed that family metaphors, light metaphors, warmth metaphors, and some war metaphors had a positive effect on patients with COVID-19. This is consistent with the recent literature [ 3 , 28 ] in that COVID-19 infection has provided a special occasion for meaning and for turning the life-threating event into a positive opportunity in fighting the disease and strengthening social relationships. Therefore, these positive metaphorical frameworks can be extensively applied to psychotherapeutic principles used in the treatment of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition to image metaphors, the present study showed that family metaphors, light metaphors, warmth metaphors, and some war metaphors had a positive effect on patients with COVID-19. This is consistent with the recent literature [ 3 , 28 ] in that COVID-19 infection has provided a special occasion for meaning and for turning the life-threating event into a positive opportunity in fighting the disease and strengthening social relationships. Therefore, these positive metaphorical frameworks can be extensively applied to psychotherapeutic principles used in the treatment of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…Negative image metaphors (e.g., plague, prisoner) were frequently used by COVID-19 patients to describe their concept of selves, suggesting that metaphors play an important role for patients to construct their identities [ 47 , 48 ]. This echoes Palese et al’s findings in that the negative-oriented metaphors used by COVID-19 patients revealed their increased vulnerability due to stigmatization and socioeconomic difficulties and the limited support received [ 28 ]. Healthcare professionals should employ positive image metaphors such as “the fighter” or “winner” in communication with COVID-19 patients in order to help them counter social stigma and to reconstruct their identities [ 16 , 24 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations